Coal Basins in the Second Polish Republic - Podolska-Meducka, Aldona (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The chapter explores interwar coal basins - the quality of coal, organisation of mining (including the functioning of extracting companies), methods of managing mines and production, and the role of foreign capital in the sector. Both bituminous coal and lignite are considered